Evolution of Nonmalignant Portal Vein Thrombosis in Liver Cirrhosis: A Pictorial Review - Xu, Shixue; Guo, Xiaozhong; Yang, Benqiang; Romeiro, Fernando Gomes [UNESP]; Primignani, Massimo; Méndez-Sánchez, Nahum; Yoshida, Eric M.; Mancuso, Andrea; Tacke, Frank; Noronha Ferreira, Carlos; De Stefano, Valerio; Qi, Xingshun (Wolters Kluwer, 2021)
Portal vein thrombosis (PVT) is a common complication in liver cirrhosis, especially in advanced cirrhosis. It may be related to a higher risk of liver-related events and liver function deterioration. Imaging examinations can not only provide an accurate diagnosis of PVT, such as the extent of thrombus involvement and the degree of lumen occupied, but also identify the nature of thrombus (i.e., benign/malignant and acute/chronic). Evolution of PVT, mainly including development, recanalization, progression, stability, and recurrence, could also be assessed based on the imaging examinations. This article briefly reviews the pathophysiology, diagnosis, classification, and evolution of PVT with an emphasis on their computed tomography imaging features.